Correlative Analysis of Radiological Measurements and 1-year SRS-22r in Early and Middle Adolescents with Adolescent Idiopathic Scoliosis: A Retrospective Study - Ermawan, Rieva; Jiwandono, Bayu Sakti; Yudistiro, Ibnu; Abdulhamid, Muhammad; Corrigan, Hubertus; Renata, Felicia ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Patient-reported outcomes are increasingly valuable for assessing the effectiveness of clinical interventions from the patient's perspective. This study aims to investigate the differences in the correlation between radiological measurements and 1-year postoperative SRS-22r domain scores in early (EA) and middle adolescence (MA) patients with adolescent idiopathic scoliosis (AIS), as well as analyze the correlation of these outcomes across different Lenke curve types. Methods: We reviewed records of 87 female AIS patients who underwent scoliosis corrective surgery, collecting data on age, body mass index, preoperative and postoperative radiographic measurements, and 1-year postoperative quality of life assessments, including function, pain, self-image, and satisfaction scores from the SRS-22r questionnaire. Patients were categorized into subgroups based on age and the number of curves. The Spearman correlation test evaluated correlations between radiographic measures and SRS-22r domain scores across these subgroups. Results: Significant correlations were found between self-image and preoperative main apical vertebral translation (AVT), Cobb angle, and trunk shift, with stronger associations in EA than MA. Pain had a weak inverse correlation with the postoperative main Cobb angle, notably in the one-curve group and more strongly in EA. Satisfaction scores decreased with age and were lower in the two-curve group and EA. Conclusions: Cobb angle correction in AIS patients strongly correlates to postoperative self-image, particularly in Lenke type 2, 3, and 6. In Lenke type 1 and type 5, greater correction of the Cobb angle is associated with increased postoperative pain.